À qui sont ces martyrs ? - Sepideh Parsapajouh (Revue des Mondes Musulmans et de la Méditerranée)
The martyrs’ divisions in Tehran’s Behesht Zahra cemetery are a major political landmark in Iran, reflecting the violent political events undergone by Iranian society. These are sacrosanct public places attracting visits from ordinary citizens. They are also the private property of the martyrs’ families and a national heritage. Different policies have been implemented by various organizations concerned with updating the landscape. These decisions, which are increasingly a matter of rationalized state oversight, have tended toward greater standardization of the graves, a standardization which is opposed by the martyrs’ families. Employing ethnographic methods, we attempt to shed light on the individual and family links between the tomb and the martyr. We then review the different political uses made of these divisions, and the emergence of militant associations seeking to defend the martyrs’ true memory and the family’s right to this memory despite its various political uses.